Case Report: Diverse phenotypes of congenital poikiloderma associated with FAM111B mutations in codon 628: A case report and literature review - Wu, Yuhao; Wen, Long; Wang, Peiru; Wang, Xiuli; Zhang, Guolong (Frontiers in Genetics, 2022)
Congenital poikiloderma is an extremely rare syndromic form of autosomal dominant poikiloderma, characterized by a combination of early onset poikiloderma, telangiectasia, and epidermal atrophy. The causative gene for congenital poikiloderma has been identified as FAM111B. In the present case report, a patient with congenital poikiloderma, which was confirmed by clinical examination was described. Genetic testing, using a gene probe consisting of 541 genetic loci of genodermatoses, was performed for the proband and his parents. The FAM111B mutation (c.G1883A) was identified in the proband. Notably, the proband and his mother both had the missense mutation in AAGAB (c.C833T), but neither had no clinical phenotypes of punctate palmoplantar keratoderma (PPPK). In conclusion, a new case of congenital poikiloderma in China has been identified in the present case report and the hotpot mutation in codon 628 in the FAM111B gene has been reviewed, as well as authenticating the uncertain association between genotypes and phenotypes in this rare disease.